2013
DOI: 10.1055/s-0033-1343396
|View full text |Cite
|
Sign up to set email alerts
|

Brustaugmentation mit autologem Fett - Erfahrungen aus 96 Operationen mit der BEAULITM-Methode

Abstract: Zusammenfassung In den letzten 30 Jahren hat das Interesse an einer Verwendung des k?rpereigenen Fettes zur ?sthetischen K?rperformung, speziell zur Augmentation der weiblichen Brust, kontinuierlich zugenommen. Fehlende Fremdk?rperreaktionen, harmonisches Aussehen und ein nat?rliches Gef?hl sind die Vorteile einer autologen Fettzell-Transplantation. Komplikationen wie Nekrosen, Infekte, Zystenbildungen, hohe Graftverluste sowie die Schwierigkeit, gro?e Fettmengen in vern?nftiger Zeit zu gewinnen boten in fr?he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…ADSC is a population of multipotent cells isolated from adipose tissue [23]. Compared with other sources of stem cells, its advantages are as follows [24][25][26][27]: ① the sources of fat are abundant, ② the patient has less pain and less damage to his donor site, ③ the isolation method of ADSC is simple and the yield is high, which is 1000 times higher than that of bone marrow stem Wexner score of patients, f VAS score of patients; Δ = Absolute value of difference in healing rate between two groups; ns = no significance, ✱✱✱ = p < 0.001, ✱✱ = p < 0.01, ✱ = p < 0.05 cells, ④ ADSC has strong ability to expand in vitro and is easy to be subcultured, ⑤ ADSC has transembryonic differentiation ability, and ⑥ immune rejection of ADSC is lower than that of other stem cells. Since Garcia-Olmo et al [28] first reported the treatment of rectovaginal fistula with adipose stem cell in 2003, this method has been a research hotspot.…”
Section: Discussionmentioning
confidence: 99%
“…ADSC is a population of multipotent cells isolated from adipose tissue [23]. Compared with other sources of stem cells, its advantages are as follows [24][25][26][27]: ① the sources of fat are abundant, ② the patient has less pain and less damage to his donor site, ③ the isolation method of ADSC is simple and the yield is high, which is 1000 times higher than that of bone marrow stem Wexner score of patients, f VAS score of patients; Δ = Absolute value of difference in healing rate between two groups; ns = no significance, ✱✱✱ = p < 0.001, ✱✱ = p < 0.01, ✱ = p < 0.05 cells, ④ ADSC has strong ability to expand in vitro and is easy to be subcultured, ⑤ ADSC has transembryonic differentiation ability, and ⑥ immune rejection of ADSC is lower than that of other stem cells. Since Garcia-Olmo et al [28] first reported the treatment of rectovaginal fistula with adipose stem cell in 2003, this method has been a research hotspot.…”
Section: Discussionmentioning
confidence: 99%
“…4 In our series, we used the Body-Jet (Human Med, Schwerin, Germany) technique, which combines water-jet-assisted liposuction, purification and grafting. 5 Regarding the fat transfer, subpectoral and epipectoral cases were treated in the same way without direct visualization of the capsule. Before the operations, ultrasound assessment of the tissue envelope was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Concentrating cells in this manner is expected to reduce postoperative volume loss [ 21 ]. Other authors advocate sedimentation [ 22 ], or washing the harvested tissue with saline and sterile gauze [ 23 ].…”
Section: Current Lipofilling Techniquesmentioning
confidence: 99%